Wykonaj mnożenia i przeprowadź redukcję wyrazów podobnych:

a) 2a(x + 5y) + 3x(a – 5y) =

b) -4b(2a – 8y) + 3y(b – 7a) =

c) (-0,4y – 4)• 5x2 – 2y(x2 – 6) =

d) 7b(5 + 3ax) – (2a – 5b) • 2bx =

e) 12(5a – 2) – 8(6a – 7b) + 3(3a – 12b) =

3

Odpowiedzi

2010-01-22T22:14:13+01:00
A) 2a(x + 5y) + 3x(a – 5y) = 2ax + 10ay +3ax -15xy = 5ax+10ay-15xy

b) -4b(2a – 8y) + 3y(b – 7a) = -8ab +32by+3by - 21ay =-8ab +35by -21y

c) (-0,4y – 4)• 5x^ – 2y(x^ – 6) =-2x^y -20x^ -2x^y+12y=-4x^y -20x^ +12y

d) 7b(5 + 3ax) – (2a – 5b) • 2bx = 35b +21abx - 4abx -10 b^x=
35b-10b^x+17abx

e) 12(5a – 2) – 8(6a – 7b) + 3(3a – 12b) =60a-24-48a+56b +9a -36b = 21a -24 +20b
1 4 1
Najlepsza Odpowiedź!
2010-01-22T22:15:02+01:00
A) 2a(x + 5y) + 3x(a – 5y) = 2ax+10ay+3ax-15xy=5ax+10ay-15xy

b) -4b(2a – 8y) + 3y(b – 7a) =-8ab+32by+3by-21ay=
=-8ab+35by-21ay

c) (-0,4y – 4)• 5x^ – 2y(x^ – 6) =-2x^y -20x^ -2x^y+12y=-4x^y -20x^ +12y

d) 7b(5 + 3ax) – (2a – 5b) • 2bx =35b+21abx-4abx-10b²x=
=35b+17abx-10b²x

e) 12(5a – 2) – 8(6a – 7b) + 3(3a – 12b) =60a-24-48a+56b +9a -36b = 21a -24 +20b
1 5 1
2010-01-22T22:40:44+01:00
A) 2a(x + 5y) + 3x(a – 5y) = 2ax+10ay+3ax-15xy=5ax+10ay-15xy
b) -4b(2a – 8y) + 3y(b – 7a) =-8ab+32by+3by-21ay=-8ab+35by-21ay
c) (-0,4y – 4)• 5x^ – 2y(x^ – 6) =-2x^y -20x^ -2x^y+12y=-4x^y -20x^ +12y
d) 7b(5 + 3ax) – (2a – 5b) • 2bx =35b+21abx-4abx-10b²x= 35b+17abx-10b²x
e) 12(5a – 2) – 8(6a – 7b) + 3(3a – 12b) =60a-24-48a+56b +9a -36b = 21a -24+20b